Alterations in sarcomere function modify the hyperplastic to hypertrophic transition phase of mammalian cardiomyocyte development - Benjamin R. Nixon; Alexandra F. Williams; Michael S. Glennon; Alejandro E. de Feria; Sara C. Sebag; H. Scott Baldwin; Jason R. Becker (JCI Insight, 2017)
It remains unclear how perturbations in cardiomyocyte sarcomere function alter postnatal heart development. We utilized murine models that allowed manipulation of cardiac myosin-binding protein C (MYBPC3) expression at critical stages of cardiac ontogeny to study the response of the postnatal heart to disrupted sarcomere function. We discovered that the hyperplastic to hypertrophic transition phase of mammalian heart development was altered in mice lacking MYBPC3 and this was the critical period for subsequent development of cardiomyopathy. Specifically, MYBPC3-null hearts developed evidence of increased cardiomyocyte endoreplication, which was accompanied by enhanced expression of cell cycle stimulatory cyclins and increased phosphorylation of retinoblastoma protein. Interestingly, this response was self-limited at later developmental time points by an upregulation of the cyclin-dependent kinase inhibitor p21. These results provide valuable insights into how alterations in sarcomere protein function modify postnatal heart development and highlight the potential for targeting cell cycle regulatory pathways to counteract cardiomyopathic stimuli.